Clinical complications in pregnant women with sickle cell disease: prospective study of factors predicting maternal death or near miss - Cardoso,Patrícia Santos Resende (2014)
OBJECTIVE: To evaluate complications in pregnant women with sickle cell disease, especially those leading to maternal death or near miss (severe obstetric complications).METHODS: A prospective cohort of 104 pregnant women registered in the Blood Center of Belo Horizonte (Hemominas Foundation) was followed up at high-risk prenatal units. They belonged to Group I (51 hemoglobin SS and three hemoglobin S/ß0-thalassemia) or Group II (49 hemoglobin SC and one hemoglobin S/ß+-thalassemia). Both groups had similar median ages. Predictive factors for 'near miss' or maternal death with p-value = 0.25 in the univariate analysis were included in a multivariate logistic model (significance set for p-value = 0.05).RESULTS: Group I had more frequent episodes of vaso-occlusive crises, more transfusions in the antepartum and postpartum, and higher percentage of preterm deliveries than Group II. Infections and painful crises during the postpartum period were similar in both the groups. The mortality rate was 4.8%: three deaths in Group I and two in Group II. One-third of the women in both the groups experienced near miss. The most frequent event was pneumonia/acute chest syndrome. Alpha-thalassemia co-inheritance and ß-gene haplotypes were not associated with near miss or maternal death. In multivariate analysis predictors of near miss or death were parity above one and baseline red blood cell macrocytosis. In Group I, baseline hypoxemia (saturation < 94%) was also predictive of near miss or death.CONCLUSION: One-third of pregnant women had near miss and 4.8% died. Both hemoglobin SS and SC pregnant women shared the same risk of death or of severe complications, especially pulmonary events.